2013
DOI: 10.4103/1463-1741.107157
|View full text |Cite
|
Sign up to set email alerts
|

Noise induced hearing loss: Research in central, eastern and south-eastern Europe and newly independent states

Abstract: The aim of this review was to summarize the studies on noise-induced hearing loss (NIHL) which were carried out in the countries of Central and Eastern Europe, South-East Europe, and former Soviet Union countries or Newly Independent States in the period from 1970 to 2012. The papers were identified by literature search of all accessible medical and other databases (Scopus, PubMed, Medline, etc.) using the terms "noise; hearing loss, NIHL" as key words and country denomination (in alphabetical order: Armenia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…It is predominantly noted in the highfrequency region, with typical notch at 4-6 kHz. 57 In this study, noise-exposed workers had a significantly higher mean threshold of hearing compared to their referent control, and more than three quarters had NIHL. Cells in the human body depend on a proper supply of oxygen and nutrients in order to maintain their functions and such supply depends on the functional and structural integrity of the heart and blood vessels.…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…It is predominantly noted in the highfrequency region, with typical notch at 4-6 kHz. 57 In this study, noise-exposed workers had a significantly higher mean threshold of hearing compared to their referent control, and more than three quarters had NIHL. Cells in the human body depend on a proper supply of oxygen and nutrients in order to maintain their functions and such supply depends on the functional and structural integrity of the heart and blood vessels.…”
mentioning
confidence: 52%
“…This integrity may be disturbed by hypertension. 57 Moreover, high BP may cause inner ear minute hemorrhages, which may cause progressive or sudden hearing loss. This circulatory system pathology may directly affect hearing in a number of ways.…”
mentioning
confidence: 99%
“…The adverse relationship between NIHL and work experience in this study can be considered an important fac- tor for hearing loss, as indicated by other investigators (33)(34)(35)(36). Years of active work was considered as the basic measure for the chronic status of noise exposure.…”
Section: Discussionmentioning
confidence: 99%
“…[12] A review on noise-induced hearing loss in Easter European States has also been published recently. [13] Although similar studies do not exist for every country, it is plausible to assume that in an enormous economic area such as the Americas, which includes Latin America, the Caribbean, Canada, and the US, work environments with high noise levels are common, and each one represents an important risk to the auditory health of the workers.…”
Section: Introductionmentioning
confidence: 98%